2013
DOI: 10.1111/ppl.12105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phenolic metabolism and primary metabolism between green ‘Anjou’ pear and its bud mutation, red ‘Anjou’

Abstract: Green 'Anjou' pear and its bud mutation, red 'Anjou' were compared to understand their differences in phenolic metabolism and its effect on primary metabolism. In the flesh of the two cultivars, no difference was detected in the concentration of any phenolic compound, the transcript level of MYB10 or the transcript levels or activities of key enzymes involved in anthocyanin synthesis. Compared with green 'Anjou', the shaded peel of red 'Anjou' had higher anthocyanin concentrations, higher transcript levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
1
21
1
1
Order By: Relevance
“…Certain studies of factors regulating anthocyanin biosynthesis have demonstrated that the protein AN2 plays an important role in determining petunia coloration (Boase et al, 2015), and that AtPAP1 and AtPAP2 regulate anthocyanin accumulation in Arabidopsis thaliana stems and leaves (Borevitz et al, 2000;Li et al, 2014). In the grapevine, VvMybA controls anthocyanin biosynthesis by modulating UFGT expression (Kobayashi et al, 2002;Dong et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain studies of factors regulating anthocyanin biosynthesis have demonstrated that the protein AN2 plays an important role in determining petunia coloration (Boase et al, 2015), and that AtPAP1 and AtPAP2 regulate anthocyanin accumulation in Arabidopsis thaliana stems and leaves (Borevitz et al, 2000;Li et al, 2014). In the grapevine, VvMybA controls anthocyanin biosynthesis by modulating UFGT expression (Kobayashi et al, 2002;Dong et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the MYB transcription factor-regulatory mechanism remains far from clear. For example, most MYB genes positively regulate anthocyanin accumulation (Chagné et al, 2013;Li et al, 2014;Lin-Wang et al, 2014), although a small number function as negative regulators (Aharoni et al, 2001;Yang et al, 2015). The transcription factor R2R3-MYB has many regulatory modes in anthocyanin biosynthesis (Wang et al, 2004;Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In apple fruit, it was reported that MdMYB10 might control both skin color and anthocyanin accumulation in fruit flesh in certain apple genotypes, whereas MdMYB1 and MdMYBA were expressed in red sections of fruit skin in other genotypes (Takos et al 2006;Ban et al 2007;Espley et al 2007Espley et al , 2009). Compared to that of non-red fruits, red apple and pear fruit peels showed higher levels of MYB transcription (Takos et al 2006;Ban et al 2007;Feng et al 2010;Lin-Wang et al 2011;Li et al 2014). In these fruits, the regulation of anthocyanin synthesis by MYB was mainly correlated with UDP-glycose:flavonoid 3-O-glycosyltransferase (UFGT), an enzyme which catalyzes the final step of anthocyanin synthesis.…”
Section: Introductionmentioning
confidence: 95%
“…Other enzymes such as phenylalanine ammonia lyase (PAL), chalcone synthase (CHS), chalcone-flavanone isomerase (CHI), flavanone-3-hydroxylase (F3H), dihydroflavonol 4-reductase (DFR), and anthocyanidin synthase (ANS) are also involved in the synthesis of anthocyanin in apple or pear peels . MYB (MdMYB1, PyMYB10, and MdMYBA) and UFGT levels, UFGT activity, and anthocyanin concentration can be enhanced by sunlight (Takos et al 2006;Li et al , 2012Li et al , 2013aLi et al , 2014Yu et al 2012) or UV irradiation (Ubi et al 2006;Ban et al 2007;Xie et al 2012) in apple or pear peels, indicating that anthocyanin synthesis is regulated by light. However, the mechanisms underlying sunlight-mediated MYB and anthocyanin synthesis are unknown.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation